STRATEGI PT. MIRAE ASET SEKURITAS DALAM MENINGKATKAN JUMLAH NASABAH (STUDI KASUS PT. MIRAE ASET SEKURITAS KANTOR CAB. BALI) - Stevany Ingrid Marta Mandosir; Putu Indah Rahmawati; Ni Kadek Sinarwati (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study is to find out the steps implemented by PT. Mirae Aset Sekuritas, to find out and analyze the final results of achieving each step that has been taken by PT. Mirae Asset Securities. This study uses qualitative research methods using SWOT analysis techniques. The research results show that the steps implemented by PT. Mirae Aset Securities Office Cab. Bali in increasing customers/investors is carrying out evaluations related to the growth of customer transactions every year, providing education to customers regarding investment behavior and disseminating information on the advantages or benefits that customers receive in using products, utilizing social media in the form of interesting video content and placing advertisements in the media social services, facilitating the process of opening an account which can be done with a mobile phone or online with a web page, using an online application, namely NAVI as an investment platform, providing services in the form of branch offices with a modern nuanced store concept and providing advantages in the form of tax free, no purchase fees -selling, portfolio diversification, liquid because the withdrawal of funds can be done at any time, and a low minimum investment value. Inhibiting factors: customer trust in the company, the presence of licensed brokerage companies that do not comply with the rules so that it has a negative impact on other investment companies Supporting Factors: the use of online applications for opening accounts that make it easier for customers to make transactions, the existence of a NAVI platform that can make it easier for customers to make mutual fund transactions from investment management.